Loss of the phospholipase C gene product induces massive endocytosis of rhodopsin and arrestin in Drosophila photoreceptors. - Orem, N.R.; Dolph, P.J. (Vision Research, 2002)
Previously we have shown that a subset of visual transduction mutants in Drosophila melanogaster induce the formation of stable complexes between rhodopsin and arrestin. One such mutant is in a visual system-specific phospholipase C (PLC). The rhodopsin/arrestin complexes generated in PLC mutants induce massive retinal degeneration. Here we demonstrate that both arrestin and rhodopsin undergo light-dependent endocytosis in a PLC mutant background. Interestingly, the internalized rhodopsin is rapidly degraded, but the arrestin is fully stable. The data are discussed with respect to mechanisms of arrestin-mediated endocytosis and human retinal disease.